Sosialisasi Bahaya Cyberbullying di Instagram dalam Konteks Perbedaan Budaya kepada Pelajar - Exsan Adde; Ramadhani Utami Dewi; Vidyardi Laksmono (Jurnal Pengabdian Kepada Masyarakat Ilmu Komunikasi, 2026)
This Community Service Program (PKM) was implemented in response to the high usage of social media among students, particularly Instagram, which often becomes a platform for cyberbullying. This phenomenon becomes increasingly complex when students come from diverse cultural backgrounds. Comments or posts considered normal in one culture may be perceived as offensive in another. A lack of cultural sensitivity often triggers digital conflict and bullying, which can negatively impact students' mental health. This PKM aims to improve students’ understanding of the dangers of cyberbullying and the importance of cross-cultural communication ethics. The program began with a pre-test to assess participants' initial knowledge, followed by an interactive seminar discussing the concepts of cyberbullying, digital ethics, and real-life case studies. Students then engaged in group discussions and simulations, where they analyzed problematic digital content and formulated empathetic, constructive responses. At the end of the activity, a post-test was conducted to evaluate the program’s effectiveness. The results showed a significant improvement in students’ awareness and attitudes. This program successfully encouraged students to be more thoughtful and responsible in their online interactions and to become change agents in creating a safer, more inclusive digital environment. The outcomes of this program include a scholarly publication, an educational video disseminated on social media, and quantitative data showing an increase in participants’ knowledge. Overall, this initiative contributes to strengthening multicultural digital literacy among today’s youth.